Rancang Bangun Sistem Informasi Penyewaan Peralatan Multimedia Pada PT. Matahari Mitra Sukses - Rezandy, Aldo Kevindra; Setyawan, Henry Bambang; Tjandrarini, A. B. (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PT. Matahari Mitra Sukses (PT. MMS) is a company engaged in the rental of multimedia equipment, located in Surabaya. Increasing the number of transactions makes PT. MMS often experiences obstacles in terms of managing bookings and rental transactions. So that all existing equipment can be calculated, monitored and known to exist, PT. MMS requires a system that can help solve the above problems by designing and building multimedia equipment rental information systems at PT. MMS. The development of this information system refers to the specifications of user needs and is continued through the stages that exist in the System Development Life Cycle (SDLC) waterfall model. Based on the results of trials that have been conducted with the Owner, this multimedia equipment rental information system can assist the Operations Section and Front Desk in managing equipment orders and equipment circulation, providing equipment recommendations for maintenance to the Operations Section. The information system can also assist the Owner in providing income reports per period, equipment lease transaction reports from partners, equipment reports with the highest leases, customer reports with the highest leases, and maintenance reports.